Knowledge And Attitudes About Organ Donation Among Commerce College Students - Shah, Rakesh; Patel, Alpesh; Ramanuj, Vaibhav; Solanki, Nitin (National Journal of Community Medicine, 2015)
Introduction: Organ transplants save thousands of lives every year. Lack of information is one of the leading causes for poor organ dona- tion. So this study was conducted to evaluate the knowledge and attitudes about organ donation among commerce college students. Materials and methods: In this cross sectional study desired informa- tion was collected from 200 students of a commerce college of Ahme- dabad using a predesigned close ended questionnaire data through face-to-face interaction. Results: Among 200 students 87.5% had heard about organ donation; 18.5% students’ relatives had donated one or more organ; 46.5% stu- dents would be willing to donate organs of a brain dead relative; 62.5% respondents like to donate their own organ; and 43.5% stu- dents were aware of parliamentary law in India regarding organ do- nation in case of brain death. Conclusion: Awareness of organ donation was high and some want to become donors. Multi-sectoral approach (e.g, electronic and print media, religious scholars, doctors and teachers) should be used to promote awareness of organ donation. Further studies are needed to motivate the general population for organ donation.